Atrial Pacing May Decrease the Incidence of Atrial Fibrillation Following Coronary Artery Bypass Graft Surgery - Cohen, M; Morin, JF; Rosengarten, M (McGill Journal of Medicine, 1996)
At the Montreal General Hospital in 1994, the incidence of atrial fibrillation (AF) following coronary artery bypass graft (CABG) surgery was 30%. With the goal of reducing the incidence of this complication, 20 patients (15 males and 5 females) undergoing CABG surgery were studied prospectively for the occurrence of AF following a three-day "on demand" atrial pacing at 90 beats- per-minute. The age range of the group was 39 to 79 years, with a mean age of 60 and a median age of 63. Two patients were categorized in NYHA class II, 13 in class III, and five in class IV. Of the latter five, two patients received intravenous nitroglycerin preoperatively. ß-blockers were taken pre- operatively by 13 patients, Ca2+ channel blockers by 12, and ACE inhibitors by two. Only one patient had suffered a myocardial infarction within the last year. Preoperative ejection fractions ranged from 15 to 60% with a mean of 45%. In all cases, the CABG operation achieved complete revascularization using left internal mammary artery (LIMA) grafts in addition to saphenous vein grafts. The average number of bypasses performed was 3.15. Cardiac arrest was induced using intermittent cold blood cardioplegia, and cardiopulmonary bypass time averaged 60 minutes. Aortic occlusion time averaged 36 minutes. Intraoperative inotrope use was infrequent, used intraoperatively with two cases requiring neosynephrine, one case requiring levophed, and one case requiring dobutamine. Post-pacing cardiac assessment revealed non-specific T wave abnormalities in five (25%) of patients, but no patient showed any evidence of acute myocardial infarction. In no cases did any complications related to the atrial pacing develop in the postoperative period. The results reveal that only two patients (15%) experienced AF following, and one during, the three-day regimen of atrial pacing. Thus, this study provides preliminary evidence of a decrease in the incidence of post-CABG AF using atrial pacing.